Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Property dan Real Estate yang Terdaftar di BEI - Dahlia Nur Muslimah; Suhendro Suhendro; Endang Masitoh (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The purpose of this study is to examine and analyze the factors that influence the capital structure. The independent variables in this study are profitability, liquidity, company size, and asset structure. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange in the period 2016-2018. The sample selection technique used in this study was purposive sampling and 34 company samples were obtained over a period of 3 years so that 102 company samples were obtained. The analytical method used in this study is multiple linear regression. The results of this study simultaneously show that profitability, liquidity, asset structure, and company size significantly influence the capital structure. The results of the research partially show that profitability, liquidity, and asset structure have an influence on capital structure, while company size has no effect on capital structure.